2015
DOI: 10.15517/rbt.v63i4.16845
|View full text |Cite
|
Sign up to set email alerts
|

Anthropic influence on the landscape of Pelliciera rhizophorae (Ericales: Tetrameristaceae) Southern-most Caribbean populations (Turbo, Colombia).

Abstract: <p><em>Pelliciera rhizophorae</em> es una especie neotropical y monotípica, listada como Vulnerable por la UICN, debido a su estrecho ámbito geográfico en América tropical y por presentar poblaciones pequeñas, dispersas y usualmente rodeadas de coberturas antrópicas. Aquí se informa el hallazgo de dos poblaciones nuevas en el golfo de Urabá (Colombia, Caribe Sur) y la dominancia antropogénica del paisaje circundante, dentro de 40.7 km<sup>2</sup> de franja costera del Sureste del … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…(likely P. rhizophorae) thrive seemingly isolated from others along the Caribbean coasts of Colombia and Panamá. Other populations within the Urabá Gulf in urban and rural settings also need urgent protection from illegal logging and mangrove clearing (Blanco-Libreros et al, 2016). P. benthamii is known to occur in less than 15 sites and it likely occurs in Cartagena's urban mangroves (Duke, 2020), therefore setting urban conservation schemes may reduce the local extinction risk by combining private, government, and citizen efforts.…”
Section: Recommendations For Conservationmentioning
confidence: 99%
See 1 more Smart Citation
“…(likely P. rhizophorae) thrive seemingly isolated from others along the Caribbean coasts of Colombia and Panamá. Other populations within the Urabá Gulf in urban and rural settings also need urgent protection from illegal logging and mangrove clearing (Blanco-Libreros et al, 2016). P. benthamii is known to occur in less than 15 sites and it likely occurs in Cartagena's urban mangroves (Duke, 2020), therefore setting urban conservation schemes may reduce the local extinction risk by combining private, government, and citizen efforts.…”
Section: Recommendations For Conservationmentioning
confidence: 99%
“…In addition, coastal wetland deterioration and loss are determinant processes for the fate of endangered species because they depend on habitat stability, a result of interacting anthropogenic and natural threats, under the current sea level rise rates (Kirwan and Megonigal, 2013). In mangroves, the remaining small patches in many regions are more prone to disappear due to deforestation (Bryan-Brown et al, 2020) while those located in the proximity to populated areas and paved roads experience greater anthropogenic edge effects (e.g., Blanco-Libreros and Estrada-Urrea, 2015;Blanco-Libreros et al, 2016;Zamprogno et al, 2016;Branoff, 2017;Hayashi et al, 2019), similar to the reported for tropical terrestrial forests (Laurance et al, 2002(Laurance et al, , 2011Taubert et al, 2018;Hansen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The interviews were conducted with experts defined through the "snowball" technique, which is a useful network sampling method to study populations hard to be accessed or studied (Bernard 2017). In this manner, there were 26 experts in total in the fields of fishing, agriculture, and tourism, which are the three main economic activities of the community (Ordõnez et al 2018).…”
Section: Ethnobotanical Data Collectionmentioning
confidence: 99%
“…The vulnerability of Pelliciera rhizophorae, indicated by the IUCN Red List, stems from the limited geographical distribution, as it has small and dispersed populations and is largely linked to the impacts generated by anthropic factors (Blanco-Libreros et al 2015). Because it is a mangrove species, its distribution is suffering reduction and anthropic pressure in coastal regions (Blanco-Libreros et al 2015;Duke 2020). Isolated populations and the low gene flow associated with anthropic pressures indicate that P. rhizophorae should be revised from Vulnerable to a higher threatened level on the IUCN List (Duke 2020).…”
Section: Use and Conservationmentioning
confidence: 99%
“…El género Pelliciera Triana y Planchon (1862), familia Tetrameristaceae, forma parte de los ecosistemas de manglar neotropicales, considerado endémico de la costa tropical del Pacífico americano hasta 1982 (Calderón-Sáenz, 1982). En el Caribe colombiano se registró por primera vez en sistemas estuarinos del departamento de Bolívar (Calderón-Sáenz, 1982, 1983, 1984 y posteriormente en Córdoba (Sánchez et al, 1997;Castillo-Cárdenas et al, 2015) y Antioquía (Blanco-Libreros et al, 2016). En el Caribe se ha registrado la presencia de poblaciones en otros países como Nicaragua (Roth y Grijalva, 1991) y Panamá (Duke et al, 1997;Dangremond y Feller, 2014).…”
unclassified